Mesoscale modelling for meteorological and air pollution applications (ANTHEM Press, 2018)
'Mesoscale Modelling for Meteorological and Air Pollution Applications' combines fundamental and practical aspects of mesoscale air pollution and meteorological modelling, including applications and evaluation approaches.